University-community Development participatory action research on digital marketing adoption by Royal animal hospital - Danuyal, M.; Ramyah, M.; Karunarathna, M.; Senadeera, N.A.S.L.; Sandunika, N.E.P.N.; Dasanayaka, N.G.K.G.N.; Prathapasinghe, P.A.U.C.; Ranmohotti, R.G.I.S.; Karunarathna, R.M.M.L.; Thilakarathne, R.M.S.I.D.; Dilogini, S. (Rajarata University of Sri Lanka, 2024)
This study investigates the adoption and preference of digital marketing tools by animal hospitals in Jaffna with the aim of enhancing awareness and utilization of digital marketing strategies among Micro Small and Medium Enterprises (MSMEs). Marketing specialization students from the University of Jaffna conducted participatory action research using narrative inquiry to gather personal stories and insights, providing qualitative data on the transformation of traditional marketing-based MSMEs into digital ecosystems. Photovoice empowered participants to capture community strengths and challenges through photography, encouraging richer discussions. Focus group discussions provide a platform for collective insights and collaborative reflection, whereas participatory mapping offers a visual representation of the spatial and social dimensions of the environment. These methodologies ensured a comprehensive, inclusive, and action-oriented research process. The findings highlight the significant challenges faced by Sri Lankan MSMEs, including competitiveness, customer engagement, cost efficiency, and market access, exacerbated by limited knowledge of digital marketing tools. Particularly for service providers such as animal hospitals, meeting customer expectations without digital proficiency remains a hurdle. The objectives of this study are to improve MSMEs' knowledge of digital aspects, enhance digital presence, and manage costs effectively through a booking system. This study contributes uniquely to the literature by focusing on animal hospitals and digital marketing, offering insights to enhance their digital presence through integrated traditional and digital approaches, such as zoom meetings and face-to-face awareness sessions, thereby supporting academic exploration and practical application of digitalization in the sector. Practical implications include creating and updating social media accounts, such as Facebook and TikTok, developing video content and sharing it through social media, promoting customer service and feedback through social media, implementing a personalized booking system, and creating a personalized website. These strategies aim to enhance customer acquisition, retention, and overall service quality at Royal Animal Hospital, facilitating their adaptation and growth in the digital age.
Keywords: Digital ecosystems; Digital marketing adoption; E-marketing tools; Micro small and medium enterprises; Participatory action research